IMPLEMENTASI STRATEGI CROSSWORD PUZZLE PADA MATA PELAJARAN IPS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS IV SD - Nadhira Isfahani; Sa'adah, Nadratul; Nazilla Wiranda; Monnader, Nelliy Gusti; Nurazizah; Sari, Susi Ratna (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the implementation of the crossword puzzle strategy in Social Studies (IPS) learning for grade IV elementary school students and to evaluate its impact on increasing student learning interest. This research used a descriptive qualitative approach with a single case study method. Data were collected through semi-structured interviews with one Social Studies teacher (G01) and one student (S01), as well as a learning interest questionnaire distributed to 14 grade IV students (S02–S15) at SDN 28 Pasa Rabaa. The questionnaire was developed based on Rahmawati's learning interest indicators, covering: (a) feeling of pleasure in learning, (b) interest in the material, (c) attention in the learning process, and (d) active student involvement. Data analysis followed the Miles, Huberman, and Saldana interactive analysis model. The results showed that the implementation of the crossword puzzle strategy was carried out in three stages: preparation, implementation, and evaluation. Based on questionnaire data, all four indicators of learning interest showed high to very high categories (76%–93%), indicating a significant positive impact. This strategy is effective in creating interactive, enjoyable, and student-centered learning. These findings are expected to enrich teachers' repertoire of active learning strategies, particularly in IPS learning at the elementary school level.